PENINGKATAN KETERAMPILAN SISWA DALAM PRAKTIK MENGOPERASIKAN SISTEM PENGENDALI ELEKTROMAGNETIK DENGAN PENERAPAN METODE TW I YANG DIPADU DENGAN METODE KOLABORATIF PADA SISWA II TITL 2 SMK NEGERI 2 CILACAP - Akhmad Mustangin (Sainteks, 2012)
The purpose of this study is to improve students' skills in the practice of operating the electromagnetic control system carried out by TWI menerapan method combined with collaborative methods. The research was carried out in class II-2 TITL during hours of practice teaching competence electromagnetic control system operates from August to October 2010. This research method is a class action research model with Kemmis and Taggart are carried out in two research cycles and each cycle consists of planning, implementation measures, observation and interpretation, as well as analysis and reflection. The subjects of this study were all students in grade II-2 TITL SMK Negeri 2 Cilacap by the number of 36 students comprising 34 boys and 2 girls. The results of this study is the increased ability of students to the competence of the electromagnetic control system operates. Performance test results that meet the KKM I cycle of 30.56% (11 students) and the second cycle with the KKM by 58.33% (21 students) Keywords: Skills students, operates the electromagnetic control system, method of TWI.